"TODAY THERE IS NO BOTTOM OR CEILING IN LITERATURE" - Sevrasevych, M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The memoirs were written in three stages: the first chapter "Roads that choose us" tells about childhood years, schooling and post-war life (when written, the compiler does not indicate, but it is understood that these are the earliest records); the second section "Metamorphoses", written in the 1980s and devoted to the work of Yuriy Mushketik as the editor-in-chief of the "Dnipro" magazine; the last, third chapter, "Bundle of Memories: Random Notes from Different Years", written by the writer in the 90s and later. The book concludes with reflections on Taras Shevchenko, a memorial essay on Anatoly Shevchenko, and the writer’s last novel, rather a fictionalized essay "Unsung Song (Marusya Churai)", written in 2018. Therefore, the arrangement of these commemorative materials was made by the writer’s daughter, also a writer, Lesya Mushketyk. Actually, you can ask her questions about the selection of material.